Endoscopic Endonasal Approach to Meckel's Cave. (23rd August 2013) - Karkas, Alexandre; Keller, Jeffrey T.; Theodosopoulos, Philip; Zimmer, Lee A.
Abstract : Objectives: External approaches to Meckel's Cave (MC) and petrous carotid artery offer excellent exposure but are associated with neurological‐cosmetic‐functional morbidities. Our aim is to describe an endoscopic approach to MC while providing anatomical relationships, predictable morbidities, and clinical applications. Methods: Four cadaveric heads (8 sides) were dissected with 0° endoscopy through transnasal‐transmaxillary‐transsphenoid‐transpterygoid approach. Results: A large maxillary antrostomy was performed and the sphenopalatine artery identified; the posterior and superior walls of maxillary sinus were removed, the pterygopalatine fossa (PPF) exposed, and the internal maxillary artery and maxillary nerve (V2) entering foramen rotundum identified. Lateral to pterygoid buttress, medial attachments of lateral pterygoid muscle were dissected, and the mandibular nerve (V3) in the infratemporal fossa (ITF) entering foramen ovale was exposed. A large sphenoidotomy was performed and cavernous carotid artery located. The Vidian was followed retrogradely until identifying foramen lacerum and then petrous carotid artery. The ophthalmic nerve (V1) was identified in the superior orbital fissure and Gasserian ganglion (GG) in MC in the petrous apex. The GG was followed posteriorly to the retrogasserian root and porus trigeminus. Conclusions: The described endoscopic approach affords the same exposure as external approaches with less morbidity. Indications include lesions of MC, PPF, ITF with minimal intracranial extension and biopsy of suspected malignant tumors in these areas. Limitations of the technique are massive intracranial tumor extension and difficulties to control bleeding in a narrow space. Morbidity will be discussed based on anatomical dissection. Illustrative clinical cases with videos will be presented to support this approach.